Intrathoracic esophageal rupture following blunt trauma chest in a ten months old girl - Ghritlaharey Rajendra; Jain Ajay; Gupta Gaurav; Kushwaha Anand (Wolters Kluwer Medknow Publications, 2006)
A 10 months old girl child was admitted on June 05 2005, with a history of blunt injury of chest and respiratory distress for 2 days. Chest skiagram showed effusion on right side of chest, with shift of mediastinum to opposite side. Right intercostal chest drainage was done for pyopneumothorax. Rupture of esophagus was suspected, when the chest drain showed milk. Water-soluble contrast study confirmed rupture of thoracic esophagus. Conservative management was successful in the form of intercostal chest drainage, broad-spectrum antibiotics, nasogastric feeding, parenteral nutrition, etc. A repeat contrast study showed no stricture or leak. At a follow up of 3 months, she is doing well. To the best of our knowledge, this is the youngest patient with blunt injury of chest, leading to intrathoracic esophageal rupture.